THE INFLUENCE OF PARENTING STYLE ON THE PROTAGONIST’S BEHAVIOR IN TODDPHILLIPS’ MOVIE JOKER - Ratna Aprillia Risqi; Susi Ekalestari (Universitas Islam Sumatera Utara (UISU), 2020)
The research focuses on the influence of parenting style on the protagonist’s behavior in Todd Phillips’ movie Joker. Arthur as the protagonist in the movie is a man who suffers from mental illness which then transforms him to be a mastermind of criminal because of parenting mistake. The theory adopted in this research is proposed by Baumrind, who classifies parenting style into four broad categories: authoritarian, authoritative, permissive and neglectful styles. This research adopts descriptive qualitative method and the data are collected from the movie script. The finding reveals that authoritarian and neglectful parenting styles lead a person to become rebellious, adopting problematic behavior and mastermind of criminal and disregarded by a society. The worst effect of parenting mistakes is that the protagonist transforms himself to be a psychopath.